2020
DOI: 10.1101/2020.01.03.894667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of spectrotemporal modulation detection for normal- and hearing-impaired listeners

Abstract: 1 2 1 3 Keywords: Spectrotemporal modulation processing; psychophysical reverse correlation; 1 4 computational modeling; sensorineural hearing loss; suprathreshold auditory processing. Abstract (141 words): 1 7 Spectrotemporal modulations (STMs) offer a unified framework to probe suprathreshold auditory 1 8 processing. Here, we introduce a novel methodological framework based on psychophysical 1 9 reverse-correlation deployed in the modulation space to characterize how STMs are detected by 2 0 the auditory sys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Two-sample t -tests showed that the RMS values were not significantly different between the groups in any of the conditions, and nor was the internal noise (all p -values > 0.05, see Table 3 ). RMS values were significantly positively correlated with the agreement percentage in both groups and under both conditions (all p -values < .001, see SI Appendix Figure S2 ), which is in line with theoretical expectations ( Murray, 2011 ; Ponsot et al, 2020 ) indicating that the more inter-trial stochastic variability, the lesser energy in the estimated kernels. In addition, measures of RMS and internal noise were independent of ASD severity levels for autistic participants (see SI Appendix Results S2 for details).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Two-sample t -tests showed that the RMS values were not significantly different between the groups in any of the conditions, and nor was the internal noise (all p -values > 0.05, see Table 3 ). RMS values were significantly positively correlated with the agreement percentage in both groups and under both conditions (all p -values < .001, see SI Appendix Figure S2 ), which is in line with theoretical expectations ( Murray, 2011 ; Ponsot et al, 2020 ) indicating that the more inter-trial stochastic variability, the lesser energy in the estimated kernels. In addition, measures of RMS and internal noise were independent of ASD severity levels for autistic participants (see SI Appendix Results S2 for details).…”
Section: Resultssupporting
confidence: 86%
“…To assess the energy of the kernels obtained, two further parameters were computed by participants and conditions. First, the root-mean-square (RMS) value was calculated for each participant’s kernel under each condition, which is a scalar of pitch perceptual filter that reflects how much individuals weight the different pitch portions in one direction or the other ( Ponsot et al., 2020 ). The higher the RMS, the more sensitive the participant is to the pitch.…”
Section: Methodsmentioning
confidence: 99%